Planning, Implementation, and Evaluation of Biology Learning on the Human Excretory System Using Canva as a Learning Medium - Andani, Putri Ayu; Wardani, Imaniah Bazlina; Husni, Rafeah (META: Journal of Science and Technological Education, 2025)
The rapid advancement of technology has led to the integration of digital tools in education to enhance student engagement and comprehension. This study examines the planning, implementation, and evaluation of biology learning on the human excretory system using Canva as an instructional medium for 11th-grade science students at SMAS Ibrahimy Wongsorejo, Banyuwangi. Employing a qualitative descriptive approach, data were collected through observations, interviews, and documentation to analyze the effectiveness of Canva in the learning process. The findings indicate that Canva facilitates structured lesson planning by providing interactive and visually appealing materials, making complex biological concepts more accessible. During implementation, students demonstrated increased engagement, creativity, and collaboration when utilizing Canva to design educational materials. Furthermore, evaluation through formative and summative assessments revealed improvements in students' understanding and retention of the subject matter. Teachers reported enhanced instructional delivery and positive student feedback regarding the use of Canva. However, challenges such as internet access and digital literacy were identified as areas requiring further attention.